Perspectives of baccharis secondary metabolites as sources for new anticancer drug candidates - Contigli, Christiane; Souza-Fagundes, Elaine Maria de; de Andrade, Warne Pedro [UNESP]; Takahashi, Jacqueline Aparecida; Oki, Yumi; Fernandes, G. Wilson (Springer Nature, 2022)
Cancer incidence and mortality are increasing worldwide, and the existing treatment protocols, which most frequently involve chemotherapy, are far from being successful for all kinds of tumors or all patients. Novel chemotherapy strategies are crucial to overcoming this issue, and secondary metabolites from plants and other biological sources are relevant in the search for new anticancer drug candidates. The genus Baccharis, mainly represented by the species B. artemisioides, B. concinna, B. coridifolia, B. dracunculifolia B. gaudichaudiana, B. grisebachii, B. latifolia, B. megapotamica, B. milleflora, B. obtusifolia, B. ochracea, B. penningtonii, B. salicina, B. scandens, and B. trimera, has been studied in experimental models, and their chemical extracts have demonstrated toxic effects on a range of tumor cells from different cancer origins, with low or no effects on healthy cells. Green propolis, whose botanical origin is B. dracunculifolia, also revealed comparable results. Some phytochemicals isolated from Baccharis extracts as well as from green propolis, such as artepillin C, baccharin, curcuphenol, drupanin, gardenin B, quercetin, and spathulenol, demonstrated remarkable anticancer activities in in vitro and in vivo preclinical laboratory studies. Interestingly, through different mechanisms of action, these bioactive compounds are capable of inhibiting tumor cell proliferation, migration and invasion, eliciting death by apoptosis, and affecting the tumor microenvironment. Nevertheless, more preclinical evidence is still required to point out candidates for clinical trials and to drive the development of new drugs to fight cancer.
Keywords: Anticancer action; Cancer cells; Cytotoxicity; Drug discovery; Natural products